Digital Competencies, AI Usage, and Informal Learning Effects on Teachers’ Effectiveness in Islamic Schools - Muhammad Kashif Majeed; Tunku Badariah Ahmad; Aizat Bind Shamssudin (Chatra: Jurnal Pendidikan dan Pengajaran, 2026)
The rapid expansion of digital technologies has reshaped teaching practices, yet their combined influence on teacher effectiveness in resource-constrained Islamic schools remains insufficiently explored. This study aims to examine how digital competencies, AI usage, and digital informal learning interact to enhance teachers’ effectiveness. A quantitative approach was employed using a cross-sectional survey design involving 440 teachers from Islamic secondary schools in Kot Addu, Pakistan. Data were analyzed using Structural Equation Modeling (SEM) to assess both direct and indirect relationships among variables. The findings indicate that digital competencies have the strongest influence on teachers’ effectiveness, followed by AI usage and digital informal learning, all of which show significant positive effects. The results suggest that digital competence serves as a foundational capability that enables teachers to utilize AI tools effectively and engage in continuous professional learning. However, disparities in infrastructure and access remain critical barriers, particularly in rural areas. While the study provides an integrated perspective on technology-enhanced teaching, its cross-sectional design and reliance on self-reported data may limit generalizability. These findings offer practical insights for designing integrated teacher development strategies in digital education contexts. Perkembangan teknologi digital telah mengubah praktik pembelajaran, namun pengaruh terpadu terhadap efektivitas guru di sekolah Islam dengan keterbatasan sumber daya masih belum banyak dikaji. Penelitian ini bertujuan untuk menganalisis bagaimana kompetensi digital, penggunaan AI, dan pembelajaran informal digital berkontribusi terhadap efektivitas guru. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei cross-sectional yang melibatkan 440 guru sekolah menengah Islam di Kot Addu, Pakistan. Data dianalisis menggunakan Structural Equation Modeling (SEM) untuk menguji hubungan langsung dan tidak langsung antar variabel. Hasil penelitian menunjukkan bahwa kompetensi digital memiliki pengaruh paling kuat terhadap efektivitas guru, diikuti oleh penggunaan AI dan pembelajaran informal digital yang juga berpengaruh positif signifikan. Temuan ini menegaskan bahwa kompetensi digital menjadi fondasi utama dalam pemanfaatan teknologi pembelajaran. Namun, keterbatasan infrastruktur dan akses masih menjadi hambatan, terutama di wilayah rural. Penelitian ini memberikan implikasi praktis bagi pengembangan strategi peningkatan kompetensi guru berbasis teknologi.